Characterization of the complete chloroplast genome sequence of Camellia oleifera in Hainan, China. Issue 2 (12th December 2017) - Zhang, Wan; Zhao, Yunlin; Yang, Guiyan; Tang, Yongcheng; Xu, Zhenggang
Abstract: Camellia oleifera, an evergreen small tree or shrub with high medicinal and ecological values, is mainly distributed in subtropical montane regions of China. In this study, complete chloroplast genome was reported for Camellia oleifera in Hainan, China. The results showed that the whole genome was 156, 996 bp in length, including a pair of inverted repeats (IRs) of 26, 025 bp, a large single copy (LSC) region of 86, 649 bp and a small single copy (SSC) region of 18, 297 bp. The genome contained a total of 115 different genes, including 81 protein-coding genes, 30 tRNA genes, and four rRNA genes. Among these genes, eight genes contain a single intron and two genes contain two introns. The total GC content of Camellia oleifera was 37.29%. The maximum likelihood phylogenetic analysis based on 21 chloroplast genomes showed that Camellia oleifera was similar to Camellia danzaiensis .